Bali Travel Package Advertisements: The Analysis of Verbal and Visual Signs - Wiyanti, Ni Luh Gede Elsa; Pratiwi, Desak Putu Eka; Santika, I Dewa Ayu Devi Maharani (Journal of Business on Hospitality and Tourism, 2021)
Advertisement is "an announcement or news online, or in a newspaper, on television, or on a poster about something such as a product, event, or job to persuade and encourage people to be interested in the goods or services offered". Verbal and nonverbal are communication tools that humans use to interact, whether it's through messages, sounds, pictures, and gestures. . This study aims to analyse the verbal and non-verbal signs used in travel advertisements and to find out the meaning of those signs. Travel advertisements aim to promote tourist attractions or destinations to tourists who are going to make a trip to Bali. The data were taken from several travel websites. The data were collected by observation method and then analysed by descriptive qualitative method. The analysis started by analysing the verbal and non-verbal signs based on the theory of semiotic by Saussure (1893). The analysis of the meaning of the verbal and non-verbal signs was done by using the theory of meaning proposed by Barthes (1977). And the analysis of colors was done by using the theory of color term proposed by Wierzbicka (1996). The result of the research shows that travel advertisements provide information for readers or tourists who are going to travel in Bali about interesting places to visit, such as romantic spots for dinner or honeymoon and natural view for the ones who love nature and adventure. The colors displayed in the advertisement express the atmosphere that will be obtained by readers or tourists. The advertisements promote Bali as wonderful place to visit and travel package offers which interesting and affordable.